Some opportunities of using xanthine oxidase inhibitors - O. V. Zhelyabina; M. S. Eliseev (Современная ревматология, 2019)
The review presents modern concepts of the role of xanthine oxidase (XO) in the pathogenesis of a number of diseases. It has been shown that XO activity can be associated with the development and progression not only of gout, but, possibly, diabetes mellitus, hypertension, and other cardiovascular diseases.The paradigm of an association of hyperuricemia (HU) with cardiovascular and chronic renal diseases has undergone certain changes — from skepticism to obtaining the evidence of its serious negative impact. Moreover, XO has been established to be a key enzyme involved in the synthesis of uric acid (UA) as a final adenine nucleotides metabolite, and is extensively present in various organs (the liver, intestine, lung, kidneys, heart, and brain) and in plasma. XO plays an important role in the synthesis not only of UA, but also in that of superoxide free radicals. There are two possible mechanisms linking metabolism and inflammation, in which UA is involved: inflammation activated by UA crystallization and generation of superoxide free radicals during its synthesis. The role of reactive oxygen species is discussed in a number of pathological conditions: induction of apoptosis/necrosis, inhibition of expression of many genes, activation of cell signaling cascades, oxidative damage to DNA and lipids, inflammation, metabolic disorders, atherosclerosis, etc. Inhibition of these mechanisms leads to a decrease in the synthesis and accumulation of UA in the bones, joints and other tissues. Accordingly, XO is a confirmed target for the treatment of gout, and, possibly, other HU-associated conditions. After introduction of a new XO inhibitor (iXO) into clinical practice, the target level of UA has can be achieved by more than 80% of patients with gout. So there is a growing interest in the assessment of the potentials of iXO for the treatment of different pathological conditions.